Powtoon based Animated Videos in Science Lessons to Improve Student Learning Outcomes in Islamic Elementery School - Titin Rahmayanti Rambe; Eva Faridah; Nurdin Bukit; Edy Surya (Pedagogik Journal of Islamic Elementary School, 2023)
This research is research and development. The ADDIE development model consists of 5 stages, namely: (1) analyze, (2) design, (3) development, (4) implementation, (5) evaluation. The research was carried out in Min 1 Medan City. The research subjects were 20 class IV students, consisting of 11 female students and 9 male students. The object in the research ispowtoon based animated video. The data collection techniques used were observation, tests and questionnaires. The data analysis techniques used are analysis of the feasibility of Powtoon based animated videos and analysis of the effectiveness of Powtoon based animation. Based on the results of material validation with a percentage of 91.68% it is categorized as feasible. Meanwhile, the media validation results were 93.49% with a decent percentage.The results of the pretest and posttest trials that were carried out using Powtoon based animated videos showed an increase in student learning outcomes. This is known from The results of the pretest were 17 students who did not complete and 3 students who completed with a percentage of 85%. Meanwhile, the results of the posttest were not as many as 1 student and 19 students who completed it with a percentage of 82%.